Упростите выражение:

а) 5х²-2у² 2у²

--------- + -----

3х 3х

б)а²-47 2

-------- - -----

а+7 а+7

в)в²+25 10в

--------- + ------

2в-10 10-2в

1

Ответы и объяснения

2013-04-23T00:43:30+04:00

а) (5x^2-2y^2)/3x+(2y^2)/3x=(5x^2/3-2*y^2/3)x+2y^2/3x=((5//3)x^2-2y^2/3)x+2y^2/3x=((5//3)x^2-(2//3)y^2)x+2y^2/3x=(5//3)x^3-(2//3)y^2x+2y^2/3x=(5//3)x^3-(2//3)y^2x+(2//3)y^2x=(5//3)x^3

 

// - знак дроби.

б) (a^2-47)/(a+7)-2/(a+7)=a-7+2/(a+7)-2/(a+7)=a-7
(a^2-47)/(a+7)=a-7+2/(a+7)

в) (b^2+25)/(2b-10)+10b/(10-2b)=((b^2+25)(10-2b)+10b(2b-10))/((2b-10)(10-2b))=(b^2*10-b^3*2+250-50b+10b*(2*b-10))/((2b-10)*(10-2b))=(b^2*10-b^3*2+250-50b+20b^2-100b)/((2b-10)*(10-2b))=(30b^2-b^3*2+250-150b)/(40b-4b^2-100)=0.5b-2.5+0/(-4b^2+40b-100)=.5b-2.5